Impact of Subsidy Removal on Supervision of Schools in Nigeria - D. M , Gregory,; Benjamin, Esenyin Adekunle (International Journal on Integrated Education, 2023)
This paper examined the impact of subsidy removal on supervision of schools in Nigeria. Secondary data collected from both print and online publications were used for the paper. The paper established that subsidy removal in Nigeria affected supervisor’s job performance and led to increment in supervision resources. The paper recommended that the federal and state government should increase funding of education and more priority should be given to schools supervision. Government should provide more buses and cars for supervisors and subsidize supervision resources to enable effective school supervision in Nigeria.